Sustainable recovery of secondary and critical raw materials from classified mining residues using mycorrhizal-assisted phytoextraction - Scotti, Adalgisa (2021)
In this work, mycorrhizal-assisted phytoextraction (MAP, Helianthus annuus–arbuscular mycorrhizal fungus Rhizophagus intraradices–Zn-volcanic ashes) was applied for the recovery of secondary and critical raw materials (SRMs and CRMs, respectively) from Joda West (Odisha, India) mine residues, within a novel multidisciplinary management strategy. Mine residues were preliminarily characterized by using advanced analytical techniques, and subsequently mapped, classified and selected using multispectral satellite Sentinel-2A images and cluster analysis. Selected mine residues were treated by MAP at laboratory scale, and the fate of several SRMs (e.g., Zn, Cr, As, Ni, Cu, Ca, Al, K, S, Rb, Fe, Mn) and CRMs (such as Ga, Ti, P, Ba and Sr) was investigated. Bioconcentration factors in shoots (BCS) and roots (BCR) and translocation factors (TF) were: 5.34(P) > BCS > 0.00(Al); 15.0(S) > BCR > 0.038(Ba); 9.28(Rb) > TF > 0.02(Ti). Results were used to predict MAP performance at larger scale, simulating a Vegetable Depuration Module (VDM) containing mine residues (1 m3). Estimated bio-extracting potential (BP) was in the range 2417 g/m3 (K) > BP> 0.14 g/m3 (As), suggesting the eventual subsequent recovery of SRMs and CRMs by hydrometallurgical techniques, with final purification by selective electrodeposition, as a viable and cost-effective option. The results are promising for MAP application at larger scale, within a circular economy-based approach.